The impact of urine storage methods on the results of quantitative bacterial culture in dog and cat - CJ Lien; SL Wang (Veterinární Medicína, 2023)
Quantitative bacterial culture (QBC) is the gold standard for determining urinary tract infections. However, the majority of urine samples were sent to a lab for further bacterial culture. Therefore, the storage condition was vital to maintain the quality and accuracy of the urine samples. The main objective of our study was to examine the urine QBC outcomes of (1) immediate culture, (2) culture after urine sample storage at ambient temperature for 24 h, and (3) culture after urine sample storage at 4 °C for 24 hours. There were 49 feline samples and 30 canine samples included in this study. All QBC samples kept at ambient temperature and refrigerator were consistent with immediate QBC in cats. Eight positive results from immediate QBC were in accordance with refrigerated results in dogs. There were ten positive results in the room-temperature sample with two false-positive results. Our study showed that storing conditions at room temperature or refrigeration for 24 h does not impact the results of QBC in cat urine samples. For dog samples, chilled samples have a higher accuracy rate than room temperature samples, although the overall agreement was still satisfactory.